Coping strategies and considerations regarding low anterior resection syndrome and quality of life among patients with rectal cancer; a qualitative interview study - Laursen, Birgitte Schantz; Sørensen, Gitte Kjær; Majgaard, Margit; Jensen, Line Byskov; Jacobsen, Karen Irene; Kjær, Dorte Kløve; Juul, Therese; Christensen, Peter; Mikkelsen, Anette Højer (Frontiers in Oncology, 2022)
.Low anterior resection syndrome (LARS) is defined as disordered bowel function following rectal resection, which is detrimental to quality of life (QoL). A recent international consensus definition of LARS stresses the importance of focusing on both the symptoms and the consequences that the symptoms have for the individual patient as studies indicate that LARS has a negative impact on patients’ QoL. However, an ongoing PROM study investigating late sequelae after rectal cancer finds that a minor proportion of patients scoring major LARS experience none or only little impact on quality of life Aim The aim of this study was to identify patients’ considerations and coping strategies to establish why the burden caused by major LARS had little or no influence on their QoL. Materials and methods This was a qualitative interview study based on 21 semi-structured individual telephone interviews with patients treated for rectal cancer. Data were analysed using a hermeneutic inspired thematic analysis. Results and conclusion Three themes emerged from the analysis; Adapting new life situation, Altering life perception and the Importance of relationships. Major LARS and its consequences following rectal cancer may be managed or altered by adopting problem-focused and emotion-focused coping strategies. Maintaining a positive attitude and having a good network of family and friends constitute a surplus, allowing patients to cope with the need for changed behaviour and appreciate the life that they have been given. Accepting that major LARS and its consequences cause limitations in life allowed patients to change their normality threshold over time.